2009
DOI: 10.1111/j.1600-6143.2009.02838.x
|View full text |Cite
|
Sign up to set email alerts
|

The Success of Continued Steroid Avoidance After Kidney Transplantation in the US

Abstract: There has been a significant increase in the use of steroid avoidance regimens as initial treatment for kidney transplant recipients. Early results of the effectiveness of this strategy has been mixed with certain prospective trials indicating increased acute rejection but population-based studies indicating similar or better graft survival as compared to steroid maintenance. We conducted a retrospective study of national registry data to evaluate risk factors for discontinuation of steroid avoidance protocols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…Shifts in the use of immunosuppressive regimens with increasing use of steroid avoidance regimens have also occurred (1). Although such regimens are deemed safe in selected patients, they are also associated with an increased risk for acute rejection with uncertain impact on long-term allograft function (2)(3)(4)(5). Calcineurin inhibitor-containing regimens have been associated with excellent graft survival rates.…”
mentioning
confidence: 97%
“…Shifts in the use of immunosuppressive regimens with increasing use of steroid avoidance regimens have also occurred (1). Although such regimens are deemed safe in selected patients, they are also associated with an increased risk for acute rejection with uncertain impact on long-term allograft function (2)(3)(4)(5). Calcineurin inhibitor-containing regimens have been associated with excellent graft survival rates.…”
mentioning
confidence: 97%
“…The identification of risk factors for AR after SAW would be most useful. Recently, Schold et al (16) reported that risk factors for restarting steroids after initial avoidance included African American race, sensitized recipients, patients with Medicaid as primary payer, retransplants, higher functional status recipients, and concomitant immunosuppression. Because this is a retrospective study based on national registry data and initiation of steroids (and not AR) was studied, it is difficult to draw conclusions from this study (16).…”
mentioning
confidence: 98%
“…The impact of these misclassifications on the results likely is minimal since the nondifferential nature of such influence tends to deflate results toward the null [20] . A recent registry analysis identified African American race, retransplants, highly sensitized recipients, recipients with Medicaid, elevated HLA mismatches and older donor age as risk factors for new initiation of steroids in DDK recipients who were initially discharged on an ESW regimen [21] . There were differences in the patterns of induction therapy used in ESW vs CSM groups under each peakPRA category.…”
Section: Discussionmentioning
confidence: 99%